Pain as semiosomatic force: The disarticulation and rearticulation of subjectivity - Larocco, Steve (Subjectivity, 2016)
Scarry's (The Body in Pain: The Making and Unmaking of the World, Oxford, New York, 1985) broke crucial ground in examining the antagonisms between pain, embodiment and language, and the isolating effects of pain as experience. This paper submits Scarry's claim that extreme pain destroys language, evades mediation, and isolates the subject to critical scrutiny, arguing instead that pain is a semiosomatic force, a form of feeling generated by imperative information about embodiment (real or imaginary) that works to disarticulate and move the subject and the social environment. Pain is not predominantly antagonistic to language; rather, pain insists on signifying, with language being only one of its performative media. What pain resists is representation, not the informational force exerted through language and other semiotic forms. Rather than unmaking language, pain disarticulates and rearticulates subjectivity, refashioning interrelations between the body, subjectivity, others, and culture in ongoing processes of largely aversive impingement, embroiling subjectivity with the imperative directives of embodied vulnerability. © 2016 Macmillan Publishers Ltd.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-246-870-419-636 tex.type: [object Object]
Keywords: dept.eng; embodiment; pain; performativity; semiotics; subjectivity